Development of Rule-based Procedural Content Generation for 2-Dimensional RPG - Chin Kim On; Ng Wai Foong; Tan Tse Guan; Rayner Alfred; Jason Teo; Ag Asri Ag Ibrahim (American Scientific Publishers, 2018)
This paper demonstrates the capabilities of developing a 2-dimensional role-playing game from scratch using only VB.net without other additional extension. Although VB.net which is usually not preferred by game developers, it has the potential to create a simple game prototype. The main aims of this project are to: test the feasibility of VB.net in developing a 2-dimensional role-playing game from scratch, and create a functional game prototype that can be used for future researches which are on procedural generation of item and users’ preference of item. This game prototype is essential to the listed researches as direct implementation of item drop mechanism is easier. Experimental results demonstrate success with all aims: VB.net is capable in developing 2-dimensional role-playing game, and a functional game prototype has been created which can be used for future researches.